Improving photoperiod insensitivity of a Thai upland rice variety by marker-assisted foreground selection - Watcharin, S.; Kanrob, P.; Charassri, N.; Nattapon, J. (International Journal of Agricultural Technology, 2020)
Global warming might increase climate variability with abnormal rainfall distributions. Photoperiod insensitive upland rice can be grown early or late in the rainy season, and to help the stabilize upland rice yields and reduce the risks to farmers. The SSR marker-assisted backcrossing method was applied to breed photoperiod insensitivity into the Thai superior upland rice variety cv. Dawk Pa-yawm as the recurrent parent. The donor parent was photoperiod insensitive Taichung 65, a japonica variety. The photoperiod insensitivity gene hd1 was identified using the RM8225 marker in seedling stage of F1, BC1F1, BC2F1 and BC2F2 plants. The photoperiod insensitive BC2F2 plants that flowered were selected during long day length. The results demonstrated successful use of genetic markers to alter the photoperiod insensitivity trait of an elite rice variety.